Toxic activation of an AAA+ protease by the antibacterial drug Cyclomarin A - Maurer, Michael; Linder, Daniela; Franke, Kamila B.; Jäger, Jasmin; Taylor, Gabrielle; Gloge, Felix; Guttzeit, Sebastian; Le Breton, Laura; Mayer, Matthias P.; Weber-Ban, Eilika; Carroni, Marta; Bukau, Bernd; et al. (Cell chemical biology, 2019)
ATP-driven bacterial AAA+ proteases have been recognized as drug targets. They possess an AAA+ protein (e.g., ClpC), which threads substrate proteins into an associated peptidase (e.g., ClpP). ATPase activity and substrate selection of AAA+ proteins are regulated by adapter proteins that bind to regulatory domains, such as the N-terminal domain (NTD). The antibacterial peptide Cyclomarin A (CymA) kills Mycobacterium tuberculosis cells by binding to the NTD of ClpC. How CymA affects ClpC function is unknown. Here, we reveal the mechanism of CymA-induced toxicity. We engineered a CymA-sensitized ClpC chimera and show that CymA activates ATPase and proteolytic activities. CymA mimics adapter binding and enables autonomous protein degradation by ClpC/ClpP with relaxed substrate selectivity. We reconstitute CymA toxicity in E. coli cells expressing engineered ClpC and ClpP, demonstrating that gain of uncontrolled proteolytic activity causes cell death. This validates drug-induced overriding of AAA+ protease activity control as effective antibacterial strategy.
Gesehen am 06.12.2021